COMPUTATIONAL INVESTIGATIONON THE STRUCTUREAND NMRCHEMICAL SHIFTS OF ENDO-CONE[CS2(p-METHYLCALlX[4]ARENE)]COMPLEX - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT The structure and NMR chemical shifts of endo-cone [CS2(p-methylcalix[4]arene))complex have been computationally investigated using 810+ force fields, semi-empirical (PM3) and ab initio (RHF/6-311G++(d,p)) calculations. The first comparison of ab initio NMR chemical shift calculations for a calix[4]arene inclusion complex with solid-state 13CNMR chemical shifts based on the 1:1 complex of p-methylcalix[4]areneswith carbon disulfide in endo-cone complexation mode has been reported. The results showed that ab initio (RHF/6-311G++(d,p))NMR calculations of the host-guest [CS2(p-methylcalix[4]arene)]complex are in good agreement with experimental solidstate NMR data.